Hernioplasty using nylon mesh for massive ventral abdominal hernia in adult bovine - SINGH, K; MAHAJAN, S K; SANGWAN, V; KUMAR, A; ANAND, A; SAINI, N S (The Indian Journal of Animal Sciences, 2012)
The study included 11 clinical cases of adult female bovines (6 cows, 5 buffaloes) weighing 325–410 kg, presented with ventral abdominal hernias. All the animals were non-pregnant and 7 animals (4 cows and 3 buffaloes) had the history of recent calving. Routine herniorrhaphy was not possible because of the massive size of the hernia ring and weak surrounding tissues. All the animals were operated for abdominal herrnioplasty in dorsal recumbency under inhalation anesthesia. Autoclaved synthetic nylon mesh was used as an onlay graft in all the cases. Nine animals (4 cows and 5 buffaloes) showed uneventful recovery with minimal postoperative complications. It was concluded that nylon mesh may be used for the repair of large abdominal hernias in adult bovines as an economic alternative to the costly prosthetic meshes.